Penguatan E-Commerce Fesyen Tas Kayu Mindi Berbasis Inovasi Desain di Bantul Yogyakarta - Susanto, Moh Rusnoto; Retnaningsih, Rahayu; Kirana, Kusuma Chandra (Universitas Komputer Indonesia, 2020)
Mindi wood is a local wood that is easy to obtain and is currently in great demand because it is easy to process for the craftsmen considering the nature of the wood with stable dimensions and not easily warped. Mindi wood is commonly used as raw material for making special handicraft items that can be adjusted according to needs because of its texture characteristics which tend to be straight and free from knots so that it tends to be smooth. 'Ruaya' is one of the home industries that focus on making fashion bags based on processed wood by prioritizing the distinctive design image of fashion bags. As a manufacturer of Wooden Fashion Bags, Ruaya focuses on maintaining the quality of its products and unique styles by continuing to innovate to develop its products. The products that are marketed to foreign markets are very diverse, namely fashion wooden bag as a superior product, wooden speakers, wooden wallets, and many other products made from Mindi wood. This study uses a qualitative descriptive approach intended to obtain a clear, objective, systematic, and accurate picture of the facts obtained related to the research objectives. This research design was chosen to provide a description of how the strategy of strengthening Mindi Wooden Fashion Bag E-Commerce based on Design Innovation. The data collection method used is the method of observation, interviews, document recording, and analysis of findings reflected in scientific expositions as a result of SME assistance in PKM Grant activities. The research results obtained include; (1) Strengthening the Mindi Wooden Fashion Bag Brand as a pioneering creative industry through E-Commerce. (2) Strengthening the E-Commerce based Marketing Communication (MARCOM) system as an effort to increase sales turnover and strengthen global market business strategies. (3) The strategy of strengthening Mindi Wooden Fashion Bag E-Commerce based on Design Innovation in Pajangan, Bantul.